Reaction of benzoxasilocines with aromatic aldehydes: Synthesis of homopterocarpans - Álvarez-Corral, Míriam; López-Sánchez, Cristóbal; Jiménez-González, Leticia; Rosales, Antonio; Muñoz-Dorado, Manuel; Rodríguez-García, Ignacio (Beilstein Journal of Organic Chemistry, 2007)
Condensation of 2H-benzo[g][1,2]oxasilocines with aromatic aldehydes in the presence of boron trifluoride affords mixtures of cis/trans 2-phenyl-3-vinylchromans with moderate yields. These can be transformed into homopterocarpans, a synthetic group of substances homologous to the natural isoflavonoid pterocarpans.

(untitled) - Hosomi, A.; Sakurai, H. (Tetrahedron Lett., 1976)

(untitled) - Chabaud, L.; James, P.; Landais, Y. (Eur. J. Org. Chem., 2004)

(untitled) - Sarkar, T. K.; Haque, S. A.; Basak, A. (Angew. Chem., Int. Ed. Engl., 2004)

(untitled) - Jiménez-González, L.; García-Muñoz, S.; Álvarez-Corral, M.; Muñoz-Dorado, M.; Rodríguez-García, I. (Chem.–Eur. J., 2007)

(untitled) - Jiménez-González, L.; Álvarez-Corral, M.; Muñoz-Dorado, M.; Rodríguez-García, I. (Chem.–Eur. J., 2006)

(untitled) - Jiménez-González, L.; Álvarez-Corral, M.; Muñoz-Dorado, M.; Rodríguez-García, I. (Chem. Commun., 2005)

(untitled) - García-Muñoz, S.; Jiménez-González, L.; Álvarez-Corral, M.; Muñoz-Dorado, M.; Rodríguez-García, I. (Synlett, 2005)

(untitled) - Decosterd, L. A.; Evans, H. S.; Msonthi, J. D.; Hostettmann, K. (Helv. Chim. Acta, 1987)

(untitled) - Furusawa, M.; Ido, Y.; Tanaka, T.; Ito, T.; Nakaya, K.; Ibrahim, I.; Ohyama, M.; Iinuma, M.; Shirataka, Y.; Takahashi, Y. (Helv. Chim. Acta, 2005)

(untitled) - Nkunya, M. H. H.; Waibel, R.; Achenbach, H. (Phytochemistry, 1993)

(untitled) - Tanaka, T.; Ito, T.; Iinuma, M.; Takahashi, Y.; Naganawa, H. (Phytochemistry, 1998)

(untitled) - Valenti, P.; Montanari, P.; Barili, P. L.; Dare, P. (Arch. Pharm., 1980)

(untitled) - Da Re, P.; Valenti, P.; Cateni, L.; Barili, P. L. (Tetrahedron Lett., 1976)

(untitled) - Rampa, A.; Bisi, A.; Belluti, F.; Gobbi, S.; Piazzi, L.; Valenti, P.; Zampiron, A.; Caputo, A.; Varani, K.; Borea, P. A.; Carrara, M. (Farmaco, 2005)

(untitled) - Valenti, P.; Fabbri, G.; Rampa, A.; Bisi, A.; Belluti, F. (Farmaco, 1997)

(untitled) - Schoning, A.; Friedrichsen, W. (Z. Naturforsch., B: Chem. Sci., 1989)

(untitled) - Chang, S. B.; Grubbs, R. H. (Tetrahedron Lett., 1997)

(untitled) - Meyer, C.; Cossy, J. (Tetrahedron Lett., 1997)

(untitled) - Yao, Q. W. (Angew. Chem., Int. Ed. Engl., 2000)

(untitled) - Scholl, M.; Ding, S.; Lee, C. W.; Grubbs, R. H. (Org. Lett., 1999)

(untitled) - Knolker, H. J.; Wanzl, G. (Synlett, 1995)